Reliability Allocation of Large Mining Excavator Electrical System Based on the Entropy Method with Failure and Maintenance Data - 胡天松 黄洪钟 王晓明 李光 高素荷 (东华大学学报（英文版）, 2014)
In the design of large mining excavator electrical system,a practical reliability allocation method was introduced to allocate system level reliability requirements into subsystem and component levels. During the reliability allocation process,factors from the fault and maintenance data were only considered in reliability allocation scheme. It could avoid the disturbance from expert experiences. The entropy method was also used to obtain weights of reliability allocation indexes of large mining excavators considering different factors. Then the failure rate allocation of subsystems and components could be completed.